Comparison of Conductivity Performance of Dragon Fruit Dye Extracted Using Water and Ethanol for Dye Sensitized Solar Cells - Zakaria, Rosnah; Hasdinor Hassan, Oskar; Zu Azhan Yahya, Muhd; Fariz Mohamad Taib, Mohamad; Malik Marwan Ali, Ab (International Journal of Engineering and Technology, 2018)
Natural pigments such as anthocyanin, carotenoid, flavonoids, and chlorophyll can be considered as promising alternative sensitizer dyes for DSSC to replace synthetic dye such as N719 because of their simple preparation technique, low cost, complete biodegradation, availability, purity grade, environmental friendliness and most importantly ability to reduce noble metal. In this work, UV-Vis spectra is used to observe the absorption spectra of different extracting solvent of dragon fruit dye. Fourier Transform Infrared Spectroscopy (FTIR) identifies the functional components of the dye while impedance spectroscopy gives the conductivity data. Dragon fruit dye extracted with ethanol had a lower absorbance at 518 nm compared to dragon fruit dye extracted with distilled water at 521 nm. The presence of carboxyl group in Betalains pigment within the range of 400 - 700 nm wavenumber promotes strong hydrogen bonding while the presence of COOH stretching vibration further confirms the carboxyl group of Betalains derivatives in dragon fruit dye. The electrical conductivity measured at room temperature (27°C), boiling point (100°C) and 130°C recorded highest value of 183 Scm-1 at 100 °C for dragon fruit dye diluted with distilled water (D-DI) while for dragon fruit dye diluted with ethanol (D-Etha) the value is 9.56 × 10-1 Scm-1 at 130°C hence showing that distilled water is the best solvent for natural dye from dragon fruit.